2020
DOI: 10.1002/chem.201904430
|View full text |Cite
|
Sign up to set email alerts
|

Activation of α‐Fe2O3 for Photoelectrochemical Water Splitting Strongly Enhanced by Low Temperature Annealing in Low Oxygen Containing Ambient

Abstract: Photoelectrochemical (PEC) water splitting is a promising method for the conversion of solar energy into chemical energy stored in the form of hydrogen. Nanostructured hematite (α‐Fe2O3) is one of the most attractive materials for a highly efficient charge carrier generation and collection due to its large specific surface area and the short minority carrier diffusion length. In the present work, the PEC water splitting performance of nanostructured α‐Fe2O3 is investigated which was prepared by anodization fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…These values are consistent with the binding energies typically reported for hematite. [43][44][45] The difference of Fe 2p spectra between Fe 2 O 3 (110) and O v _Fe 2 O 3 (110) films is negligible. On the other hand, significant changes are detected for O 1s spectra of both samples as displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These values are consistent with the binding energies typically reported for hematite. [43][44][45] The difference of Fe 2p spectra between Fe 2 O 3 (110) and O v _Fe 2 O 3 (110) films is negligible. On the other hand, significant changes are detected for O 1s spectra of both samples as displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the same direction, a recent study reported the enhanced performance of Fe 2 O 3 photoanodes aer thermal annealing in a low oxygen atmosphere, showing that oxygen vacancies improved the transport of photogenerated holes. 89 Theoretical Density Functional Theory (DFT) studies have also been focused on the effect of oxygen vacancies on the overpotential and nal performance of Fe 2 O 3 photoanodes. It has been reported that the most efficient way to reduce the overpotential in hematite photoanodes relies on the control of the population of oxygen vacancies.…”
Section: Hematite Fe 2 Omentioning
confidence: 99%
“…In order to deal with the energy crisis and greenhouse effect caused by fossil energy dependence, hydrogen production from photoelectrochemical (PEC) water splitting has become an effective countermeasure. In the PEC water decomposition systems, the performance of the photoanodes has a decisive effect on the efficiency. , Among the available photoanode materials, BiVO 4 has attracted significant attention because of its suitable energy band structure, long carrier lifetime, and low cost, but it suffers from serious recombination of photogenerated carriers on the bulk phase and semiconductor surface. , The introduction of oxygen vacancy can ameliorate the performance of metal oxide photoanodes in various ways, such as broadening the absorption range, adjusting the energy band structure, increasing the carrier mobility, and increasing the oxygen evolution activity of the material surface, which have been explored in a variety of oxide photoanodes such as Fe 2 O 3 , TiO 2 , ZnO, WO 3 , and BiVO 4 . Oxygen vacancies are also favorable for other photocatalytic processes such as CO 2 reduction reaction and N 2 fixation . Theoretical calculations showed that for the (010) plane of BiVO 4 , the Bi atoms are the active oxygen evolution sites in BiVO 4 , and the V atoms can become active sites only when oxygen vacancies exist.…”
Section: Introductionmentioning
confidence: 99%